Theoretical and experimental studies of IR spectra of 4-aminopyridine metal(II) complexes - Büyükmurat, Y.; AKYÜZ, SEVİM (Elsevier, 2003)
In this study FT-IR spectra of M(L)2Ni(CN)4 {where M=Fe or Zn, L=4-aminopyridine} complexes are reported for the first time in the 400–4000 cm−1 range. The spectral features suggest that the compounds are similar in structure to the Hofmann-type complexes with infinite polymeric layers formed with Ni(CN)4−2 ions bridged by M(L)2+2 cations. IR frequency shifts, upon formation of coordination compound are reliable indicators of the coordination mode of 4-aminopyridine. It is concluded that the ring nitrogen and not the amino nitrogen is involved in complex formation. In order to investigate metal–ligand coupling peculiarities, the vibrational wavenumbers of free and coordinated 4-aminopyridine have been calculated by a force field refinement method. The results indicated that the force field of free 4-aminopyridine should be altered in complex formation in order to represent the experimental data.
Keywords: Aminopyridine; Tetracyanonickelate complexes; Normal coordinate analysis; Force field refinement; IR spectrum